Hi,

Please help.

Prove that:

(sin θ-kos θ+1)/(sin θ+kos θ-1)= (sin θ+1)/(kos θ)

(kos θ/ 1-tan x) + (sin θ/1-kot θ) = sin θ + kos θ

Solve that tanx = π - 2x , 0<x<π/2

Thnks. :D

Printable View

- Sep 5th 2013, 07:12 AMShaynaProve!
Hi,

Please help.

Prove that:

(sin θ-kos θ+1)/(sin θ+kos θ-1)= (sin θ+1)/(kos θ)

(kos θ/ 1-tan x) + (sin θ/1-kot θ) = sin θ + kos θ

Solve that tanx = π - 2x , 0<x<π/2

Thnks. :D - Sep 5th 2013, 07:44 AMred_dogRe: Prove!
1)

2)

I don't understand the last part of the problem - Sep 5th 2013, 09:10 AMShaynaRe: Prove!
Thank you. May I know how (sinθ/2 = cos θ/2)^2 = 1+sin θ ?this part I m not understanding.

- Sep 5th 2013, 09:26 AMShaynaRe: Prove!
Hi, I got it. Thank you very much for ur help! =D

- Sep 5th 2013, 08:46 PMibduttRe: Prove!
Alternatively we can also get the solution as indicated

Attachment 29123 - Sep 6th 2013, 12:26 AMShaynaRe: Prove!
hi,

SORRY, I can't get the steps at line 2. sec^2 x -tan - Sep 6th 2013, 12:27 AMShaynaRe: Prove!
hi,

SORRY, I can't get the steps at line 2. sec^2 x -tan^2 x -----> 1-(sec x -tan x) ? TQ. - Sep 6th 2013, 01:59 AMibduttRe: Prove!
It was (sec x +tan x ) -1 = ( sec x - tan x ) - ( sec^2 x - tan^2 x ) .... Because sec^2 x -tan^2 x = 1

= ( sec x - tan x ) - (( sec x - tan x ) ( sec x +tan x ) )= ( sec x +tan x ) [ 1 - ( sec x - tan x ) ] etc